Suture button reconstruction of the central band of the interosseous membrane in Essex-Lopresti lesions: a comparative biomechanical investigation. (May 2017) - Hackl, M.; Andermahr, J.; Staat, M.; Bremer, I.; Borggrefe, J.; Prescher, A.; Müller, L. P.; Wegmann, K.
Surgical reconstruction of the interosseous membrane may restore longitudinal forearm stability in Essex-Lopresti lesions. This study aimed to compare the longitudinal stability of the intact forearm with a single-bundle and a double-bundle reconstruction of the central band of the interosseous membrane using digital image correlation with a three-dimensional camera system. Single and cyclic axial loading of eight fresh-frozen forearm specimens was carried out in the intact state, after creation of an Essex-Lopresti lesion, after a single-bundle and after a double-bundle reconstruction of the central band using a TightRope ® (Arthrex GmbH, Munich, Germany) construct. Instability significantly increased after creation of an Essex-Lopresti lesion. The stability of intact specimens was similar to both reconstruction techniques. The results of this study suggest that TightRope ® reconstruction of the central band restores longitudinal forearm stability. However, the single-bundle technique may be less reliable than double-bundle reconstruction. Level of evidence: Basic Science Study